2007
DOI: 10.1007/s00467-006-0396-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging strategies for vesicoureteral reflux diagnosis

Abstract: The prevalence of vesicoureteral reflux (VUR), although reported to be low in the general population, is high in children with urinary tract infection (UTI), first degree relatives of patients with known VUR and children with antenatal hydronephrosis. In addition, it has been shown that VUR and UTIs are associated with renal scarring, predisposing to serious long-term complications, i.e., hypertension, chronic renal insufficiency and complications of pregnancy. Therefore, diagnostic imaging for the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 92 publications
(125 reference statements)
0
20
0
4
Order By: Relevance
“…Dick PT and Feldman W in an evaluation of 434 publications through a systematic overview concluded that the current recommendations are not based on firm evidence (10). Many authors have to find a better way for detecting VUR and reduce invasiveness of the procedures (11)(12)(13)(14). We found evidence for extensive efforts in the medical literature trying to diagnose VUR without radiation and catheterization.…”
Section: Imaging Studiesmentioning
confidence: 84%
“…Dick PT and Feldman W in an evaluation of 434 publications through a systematic overview concluded that the current recommendations are not based on firm evidence (10). Many authors have to find a better way for detecting VUR and reduce invasiveness of the procedures (11)(12)(13)(14). We found evidence for extensive efforts in the medical literature trying to diagnose VUR without radiation and catheterization.…”
Section: Imaging Studiesmentioning
confidence: 84%
“…Some studies have reported that renal damage is associated with high-grade VUR without urinary tract infection (17), whereas others have reported that VUR does not cause renal scarring in the absence of urinary tract infection (18). The small number of patients and refluxing units in our study might obscure the possible association between the new quantitative parameters and renal and patient outcome.…”
Section: Discussionmentioning
confidence: 69%
“…Genellikle süt çocukluğundan sonra tanı alırlar. Üriner enfeksiyon geçirmek sekonder renal skar gelişmesi için önemli bir risk faktörüdür (52).…”
Section: Reflü Nefropatisiunclassified